2020
DOI: 10.1111/oik.06960
|View full text |Cite
|
Sign up to set email alerts
|

Structural defence is coupled with the leaf economic spectrum across saplings of spiny species

Abstract: Given that the rate of resource capture constrains plant growth and defence, understanding the linkage between the leaf economic spectrum (LES) and defence and how it contributes to growth is central to predicting species performance. In spite of the prevalence of spiny plants in many plant communities, little is known about how the LES relates to defence and growth rate across these species. We grew 42 spiny species, from diverse environments, under common garden conditions for 15 weeks and measured LES (leaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 99 publications
0
22
3
Order By: Relevance
“…Similarly, across species of spiny plants, physical defenses are associated with leaf productivity, whereas chemical defenses are not (Armani et al 2020). Both chemical and physical defense traits are correlated with LES traits within Asclepias syriaca, but not among different Asclepias species (Agrawal 2020).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, across species of spiny plants, physical defenses are associated with leaf productivity, whereas chemical defenses are not (Armani et al 2020). Both chemical and physical defense traits are correlated with LES traits within Asclepias syriaca, but not among different Asclepias species (Agrawal 2020).…”
Section: Discussionmentioning
confidence: 97%
“…This point can be exemplified by the presence of spines in many species of Euphorbia . Spines are thought to predominantly function as a defence against vertebrate herbivores (Cooper & Owen‐Smith, 1986; Burns, 2014; Wigley et al ., 2015; Charles‐Dominique et al ., 2016; Tomlinson et al ., 2016; Armani et al ., 2020). The latter is identified as a neutral trait in our analysis, indicating that it is not aligned with the climate groups we tested here.…”
Section: Discussionmentioning
confidence: 99%
“…Plant anti-herbivore secondary metabolites (i.e., phenolics) and plant structural components (i.e., cellulose and lignin) are important in affecting insect development. For example, lignin, as an important predictor of leaf toughness, can decrease arthropod damage, even at relatively low amounts ( Ohmart and Edwards, 1991 ; Steinbauer et al, 1998 ; Armani et al, 2020 ). Our results indicated that lignin content is a significant defense strategy, suggesting that potato tuberworm larvae develop better in S. tuberosum plants with low lignin, but worse in L. barbarum with high lignin.…”
Section: Discussionmentioning
confidence: 99%